2014
DOI: 10.1371/journal.pone.0104123
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Color Fluorescence Imaging to Monitor CYP3A4 and CYP3A7 Expression in Human Hepatic Carcinoma HepG2 and HepaRG Cells

Abstract: Human adult hepatocytes expressing CYP3A4, a major cytochrome P450 enzyme, are required for cell-based assays to evaluate the potential risk of drug-drug interactions caused by transcriptional induction of P450 enzymes in early-phase drug discovery and development. However, CYP3A7 is preferentially expressed in premature hepatoblasts and major hepatic carcinoma cell lines. The human hepatocellular carcinoma cell line HepaRG possesses a high self-renewal capacity and can differentiate into hepatic cells similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…It has been classified as a bipotent hepatic progenitor cell line that can be differentiated into both cholangiocyte-like and hepatocyte-like cells (Parent et al, 2004). Many studies have demonstrated that HepaRG-derived hepatocytelike cells exhibit properties of adult human hepatocytes, including the expression of xenobiotic-metabolizing enzymes, transporters, and the transcription factors that control hepatocellular gene expression (Aninat et al, 2006;Lubberstedt et al, 2011;Gerets et al, 2012;Hoekstra et al, 2013;Tsuji et al, 2014). Undifferentiated and differentiated HepaRG cells have distinct gene expression profiles that tend to reflect the patterns seen in fetal and adult human liver, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been classified as a bipotent hepatic progenitor cell line that can be differentiated into both cholangiocyte-like and hepatocyte-like cells (Parent et al, 2004). Many studies have demonstrated that HepaRG-derived hepatocytelike cells exhibit properties of adult human hepatocytes, including the expression of xenobiotic-metabolizing enzymes, transporters, and the transcription factors that control hepatocellular gene expression (Aninat et al, 2006;Lubberstedt et al, 2011;Gerets et al, 2012;Hoekstra et al, 2013;Tsuji et al, 2014). Undifferentiated and differentiated HepaRG cells have distinct gene expression profiles that tend to reflect the patterns seen in fetal and adult human liver, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Undifferentiated and differentiated HepaRG cells have distinct gene expression profiles that tend to reflect the patterns seen in fetal and adult human liver, respectively. Genes that are primarily expressed in fetal hepatocytes, such as CYP3A7 and pyruvate kinase muscle isozyme, are more highly expressed in undifferentiated HepaRG cells, whereas genes that are predominantly expressed in adult hepatocytes, such as CYP3A4 and CYP2E1, are more highly expressed in differentiated HepaRG cells (Tsuji et al, 2014;Bucher et al, 2017). HepaRG cells are becoming established as a useful model for studying hepatocellular differentiation, xenobiotic metabolism and toxicity, and development of liver diseases (Sharanek et al, 2015;Nunn et al, 2016;Rodrigues et al, 2016;Sayyed et al, 2016;Xia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression units were placed between insulator sequences (INS) to prevent inappropriate inactivation by position effects. A loxP site was also placed into the vector, facilitating easy integration of a single copy vector into an acceptor loxP site previously placed in a specific chromosomal region of the host cell genome by Cre-mediated site-specific recombination [ 19 ]. The ORFs of G-Luc and C-Luc with KDEL were amplified using 3’ reverse primers containing the 12-base sequence encoding KDEL ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This means that a decreased gastrointestinal transit time caused by rotavirus infection forces the metabolism of tacrolimus in lower intestinal tissue . Oxidation of 50–60% of clinical drugs is through CYP3A4 enzyme . CYP3A4 is highly expressed at the apex of the villus enterocytes adjacent to the microvillus border, whereas the crypt cells have null expression.…”
Section: Introductionmentioning
confidence: 99%